DESKRIPSI PENERAPAN STANDAR PROSES DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP KOTA PALU - Syahril Syahril; Nur Korompot (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2016)
This study discusses Implementation Management Principals of MTs Negeri West Palu in Improving the Quality of Learning Islamic Education. This research was motivated by concern about the low quality of Islamic education institutions in Indonesia, especially in madrasah. Madrasah is one institution of Islamic formal`s education, has been widespread in all regions of the republic of Indonesia. Quantitatively, this agency has been encouraging. But in terms of quality is still a concern largely because the quality is still considered low. One reason for the low quality of education is the unprofessional management s. Therefore, researchers interested in conducting research on one of MTs negeri in the city of Palu, Central Sulawesi. This study is a qualitative research, with data collection methods used are: observation, interviews, documentation, and triangulation. The results showed that the management of madrasah tsanawiyah Negeri west Palu has been managed by implementing modern management, that are: Manajemen Berbasis Sekolah (MBS) dan Kurikulum Tingkat Satuan Pendidikan (KTSP). The conclusion is the MTs Negeri West Palu has experienced encouraging quality improvement, both from the academic and non-academic as evidenced by the acquisition of A+ Accreditation value rankings. The achievement would be retained by the headmaster and colleagues in the wiews. Thus M.TsN West Palu included in one of the Islamic educational institutions that have a good quality in Indonesia